2023
DOI: 10.3390/ani13060969
|View full text |Cite
|
Sign up to set email alerts
|

Paired Analysis of D-Dimer and Its Correlated Hemostatic Parameters in 30 Dogs with Neoplasms after Tumorectomy

Abstract: Previous studies have reported that dogs with neoplasms had elevated D-dimer levels. However, few studies have addressed whether D-dimer could be an indicator of tumor burden. The clinical significance of paired analysis of pre- and post-operation of D-dimer levels in dogs has rarely been described. The present study investigated the values of D-dimer levels and their correlated hemostatic alterations in dogs with surgically removable benign and malignant tumors. This study analyzed 30 clinically healthy and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
(68 reference statements)
1
2
1
Order By: Relevance
“…The main pathophysiological mechanisms of DIC that develop are a consequence of crosstalk between the coagulation and inflammatory host-defense systems and secondary imbalances in pro-and anticoagulant factors. Dogs with tumors usually exhibited elevated levels of D-dimers [55,56]. As reported in our study, no statistically significant variations in D-dimer concentration were found between dogs with lymphoma and control dogs, nor between the various stages of the neoplastic disease, although the values tend to increase with the stage of the disease.…”
Section: Discussionsupporting
confidence: 61%
“…The main pathophysiological mechanisms of DIC that develop are a consequence of crosstalk between the coagulation and inflammatory host-defense systems and secondary imbalances in pro-and anticoagulant factors. Dogs with tumors usually exhibited elevated levels of D-dimers [55,56]. As reported in our study, no statistically significant variations in D-dimer concentration were found between dogs with lymphoma and control dogs, nor between the various stages of the neoplastic disease, although the values tend to increase with the stage of the disease.…”
Section: Discussionsupporting
confidence: 61%
“…One study reported abnormal coagulation parameters in dogs with tumors, such as hyperfibrinogenemia 36 . Dogs with tumors often present with abnormal hemostatic parameters, including increased fibrinogen concentrations 37 . However, these previous studies focused on reporting abnormal coagulation tests or hemostatic alterations in dogs with neoplastic diseases, and the clinical relevance and utility of DR‐70 concentrations were rarely described.…”
Section: Discussionmentioning
confidence: 99%
“…36 Dogs with tumors often present with abnormal hemostatic parameters, including increased fibrinogen concentrations. 37 However, these previous studies focused on reporting ). We used the WHO grading system to grade these samples.…”
Section: Increased Dr-70 Concentrations In Dogs With Inflammation And...mentioning
confidence: 99%
“…It is reported that the d-dimer concentration wasn't affected by lithium heparin and sodium citrate (Wauthier et al, 2023). When a comparison was made for d-dimer concentration in dog blood collected in EDTA and sodium citrate, the concentration of d-dimer was observed to be elevated (Ke et al, 2023).…”
Section: D-dimer Concentrationmentioning
confidence: 98%
“…When HbA1c value remains stable when measured from blood collected with sodium heparin, lithium heparin, EDTA, sodium citrate, and sodium fluoride, these anticoagulants do not affect HbA1c value. This is because the RBCs are lysed before the test is conducted (Ke et al, 2023;Kiefer et al, 2018;Wauthier et al, 2023).…”
Section: Changes In Blood Glucose Concentrationmentioning
confidence: 99%